Interleukin-33 Promotes Cell Survival via p38 MAPK-Mediated Interleukin-6 Gene Expression and Release in Pediatric AML - Wang, Yiqian; Su, Haibo; Yan, Muxia; Zhang, Li; Tang, Jiancheng; Li, Quanxin; Gu, Xiaoqiong; Gong, Qing (Frontiers in Immunology, 2020)
Acute myeloid leukemia (AML) is a fatal disease characterized by the accumulation of immature myeloid blasts in the bone marrow (BM). Cytokine provide signals for leukemia cells to improve their survival in the BM microenvironment. Previously, we identified interleukin-33 (IL-33) as a promoter of cell survival in a human AML cell line and primary mouse leukemia cells. In this study, we report that the cell surface expression of IL-33-specific receptor, Interleukin 1 Receptor Like 1 (IL1RL1), is elevated in BM cells from AML patients at diagnosis, and the serum level of IL-33 in AML patients is higher than that of healthy donor controls. Moreover, IL-33 levels are found to be positively associated with IL-6 levels in pediatric patients with AML. In vitro, IL-33 treatment increased IL-6 mRNA expression and protein level in BM and peripheral blood (PB) cells from AML patients. Evidence was also provided that IL-33 inhibits cell apoptosis by activating p38 mitogen-activated protein kinase (MAPK) pathway using human AML cell line and AML patient samples. Finally, we confirmed that IL-33 activated IL-6 expression in a manner that required p38 MAPK pathway using clinical AML samples. Taken together, we identified a potential mechanism of IL-33-mediated survival involving p38 MAPK in pediatric AML patients that would facilitate future drug development.